Surgical Strategies and Outcomes for Intracranial Chondromas: A Retrospective Study of 17 Cases and Systematic Review - Liu, Hongyuan; Cai, Qing; Li, Junting; Xue, Yafei; Zhang, Yunze; Li, Zongping; Zhao, Tianzhi; Wu, Yingxi (Frontiers in Oncology, 2022)
Objective: To improve the diagnosis and treatment of intracranial chondromas (ICDs) by discussing the clinical manifestations and imaging characteristics of ICDs, as well as surgical methods and treatment strategies. Methods: We retrospectively analyzed 17 patients diagnosed with ICDs who underwent microsurgery or endoscopic transsphenoidal surgery at the Tangdu Hospital of Air Force Military Medical University and the Mianyang Central Hospital from January 2010 to November 2021. Clinical manifestations, imaging examinations, surgical treatments, and prognosis of these patients were analyzed. Results: ICDs had often been misdiagnosed as craniopharyngioma, chordoma, schwannoma, cavernous hemangioma, pituitary adenoma, and meningioma before surgery. Of the 17 cases, gross total resection (GTR) was performed in 10 cases, subtotal resection (STR) in 5, and partial resection in 2. GTR of tumor was achieved in eight cases via the endoscopic endonasal transsphenoidal approach (EETA) or the extended endoscopic endonasal transsphenoidal approach (EEETA), and the remaining patients underwent craniotomies. Clinical symptoms were assessed 1 week after surgery, 10 cases were relieved at varying degrees, and four cases had no improvement. Postoperative complications included right-limb hemiparesis, diplopia, eyelid ptosis, pulmonary infection, subcutaneous hydrops, cerebrospinal-fluid leakage (CSFL), and intracranial infection (ICI). One patient received gamma knife treatment at 3 months after surgery, two patients died due to tumor progression, and the remaining patients had no tumor recurrence. Conclusions: ICDs lack typical imaging features and are often misdiagnosed. The EETA or EEETA helps improve the surgical outcomes and GTR rates of ICDs at different sites.